Enhancing Maintenance Services Quality: A Study of Student Satisfaction and Maintenance Strategies in Student’s Residential College - Mohd Midha, Amirul Hafizi Mohd Midha; Mustafa, Mohd Syafiq Syazwan; Zakaria, Anies Faziehan; Yusof, Fatimah; Musa, Kamaruzaman; Abdul Rahman, Ashraf; Abd Latif, Muhamad Faiz; Wijayaningtyas, Maranatha; Jumat, Ahmad Rusyaidi (semarak ilmu, 2024)
Maintenance services play a pivotal role in maintaining existing facilities, structures, buildings, and real property, encompassing routine maintenance, repairs, and replacement. In the contemporary landscape, the quality of maintenance has emerged as a critical factor in ensuring the optimal function of buildings and their components. This research endeavors to ascertain the perceived levels of students’ satisfaction and expectation towards the quality of maintenance services at the residential college of Universiti Tun Hussein Onn Malaysia Pagoh Campus. This study also aimed to delineate maintenance strategies that leverage several technologies to enhance maintenance service quality. Through questionnaires, this study collected responses from a sample of participants and employed SERVQUAL approach, comprising five distinct elements, for analysis. Findings indicated that students' expectation and satisfaction levels, particularly in the realms of reliability, tangibles, and assurance, yielded high scores. However, responsiveness and empathy recorded comparatively lower scores. Additionally, the Importance Index (I) analysis measured the significance of maintenance strategies and revealed that all identified strategies were not only essential but also of paramount importance. The primary contribution of this study lies in the implementation of SERVQUAL model, which explained the relationship between maintenance service quality and various strategies employed. Recognizing the pivotal role of maintenance service quality in influencing student productivity, this study provides valuable insights for public institutions to enhance their maintenance services. The institutions can effectively elevate maintenance service quality towards advanced technology by emphasizing strategies that align with the five SERVQUAL elements.